1984
DOI: 10.1002/jcb.240240302
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte receptors for antithrombin III‐proteinase complexes

Abstract: The in vivo clearance of antithrombin III-proteinase complexes occurs via a specific and saturable pathway located on hepatocytes. We now report studies of the catabolism of antithrombin III-proteinase complexes in vitro using rat hepatocytes in primary culture. Antithrombin III-thrombin and trypsin complexes were prepared and purified to homogeneity. Ligand uptake by hepatocytes was concentration, temperature, and time dependent. Initial rate studies were performed to characterize the maximum rate of uptake, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

1984
1984
1997
1997

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 39 publications
0
10
1
Order By: Relevance
“…In addition, the uptake of ATIII-trypsin complexes was accompanied by the formation of a disulfide interchange product between the ligand and a cellular protein [18]. A similar observation has been made with insulin, which undergoes disulfide interchange with the insulin receptor [ 191. In the present report, the catabolism of alPI-trypsin complexes was studied in vitro using rat hepatocytes in primary culture.…”
mentioning
confidence: 60%
“…In addition, the uptake of ATIII-trypsin complexes was accompanied by the formation of a disulfide interchange product between the ligand and a cellular protein [18]. A similar observation has been made with insulin, which undergoes disulfide interchange with the insulin receptor [ 191. In the present report, the catabolism of alPI-trypsin complexes was studied in vitro using rat hepatocytes in primary culture.…”
mentioning
confidence: 60%
“…Subsequent studies demonstrated uptake of radiolabeled serpin-enzyme complexes by hepatocytes (24,25). Cross-competition experiments in vivo suggested that complexes containing ␣1-antitrypsin, ␣1-antichymotrypsin, antithrombin, or heparin cofactor II are cleared by the same hepatic receptor (26,27), whereas ␣2-antiplasmin-protease complexes are eliminated by a different mechanism (28).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were then washed in 0.1% BSA-PBS supplemented with 1 mM CaCl 2 . Primary rat hepatocytes were isolated and cultured as detailed previously (29). PMN and monocytes used for flow cytometric and radioreceptor binding experiments were prepared, cultured, and harvested as described previously (26).…”
Section: Methodsmentioning
confidence: 99%
“…Tetrameric C1-INH⅐C1 s⅐C1 r⅐C1-INH complexes were prepared using a procedure described by Ziccardi and Cooper (28). Complexes of ␣ 1 -AT-trypsin or ␣ 1 -AT-elastase were prepared and purified as described (29 (32). Immunostaining was performed with a polyclonal antibody against the COOH-terminal C1-INH peptide and alkaline phosphatase-conjugated polyclonal goat IgG antibodies against rabbit IgG (Sigma), followed by a color reaction using 5-bromo-4-chloro-3-indolyl phosphate and nitro blue tetrazolium chloride.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation